Community policing in Kakuma camp, Kenya - Brankamp, H (Refugee Studies Centre, University of Oxford, 2016)
Community policing has become a popular way of promoting local ownership of security in refugee camps in Kenya and more widely, but it can also fall victim to its ambivalent position at the intersection of refugee communities and state policing.